(untitled) (Scientific journal of the Fergana State University, 2022)
This article discusses the unique features of the artistic prose of the unique creator Isajon Sultan, the stable word combinations used in his works, proverbs, the place of poetry in the artistic text, the writer’s skill in using language tools in his methods and methods of describing reality